Keefektifan Metode Pembelajaran Kooperatif Model STAD Ditinjau dari Prestasi dan Motivasi Belajar Siswa di Kelas VIII SMP - Badrun Badrun; Hartono Hartono (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2013)
Penelitian ini bertujuan untuk mengungkapkan (1) keefektifan pembelajaran kooperatif model STAD (2) keefektifan pembelajaran konvensional ditinjau dari prestasi dan motivasi belajar siswa, serta (3) perbandingan keefektifan pembelajaran kooperatif model STAD dengan pembelajaran konvensional ditinjau dari peningkatan prestasi dan motivasi belajar siswa. Penelitian ini dilaksanakan di SMP Negeri 4 Gamping, Sleman, Yogyakarta. Populasi penelitian ini adalah 215 siswa kelas VIII semester genap tahun pelajaran 2012/2013. Sampel penelitian ini adalah 36 siswa kelas VIII E sebagai kelompok eksperimen dan 35 siswa kelas VIII C sebagai kelompok kontrol. Data dianalisis dengan uji manova, one sample t-test, dan independent sample t-test. Hasil penelitian menunjukkan bahwa: (1) pembelajaran kooperatif model STAD efektif ditinjau dari prestasi dan motivasi belajar siswa,(2) pembelajaran konvensional tidak efektif ditinjau dari prestasi tetapi efektif ditinjau dari motivasi belajar siswa, dan (3) pembelajaran kooperatif model STAD lebih efektif dibandingkan pembelajaran konvensional ditinjau dari peningkatan prestasi belajar siswa tetapi tidak lebih efektif ditinjau dari peningkatan motivasi belajar.Kata Kunci: STAD, prestasi, motivasi belajar. The Effectiveness of the STAD Type Cooperative Learning Method and Motivation Viewed from Students’ Achievement in Class VIII SMP AbstractThis study aims to describe (1) the effectiveness of cooperative learning model of STAD, (2) the effectiveness of conventional teaching model, and (3) describe the comparison between the effective-ness of cooperative learning model of STAD and the conventional teaching model seen from the performance improvementin terms of students’ achievement and learning motivation. This research was conducted at SMP Negeri 4 Gamping, Sleman, Yogyakarta. The population is 215 year-eight students in their second semester in 2012/2013. A sample of 36 students of class VIII E as an experimental group and 35 students of class VIII C as control group. Data were analyzed using the manova test, one sample t-test, and independent sample t-test. The results show that: (1) the STAD type cooperative learning model effective in terms of students’ achievement and learning motivation, (2) the conventional teaching is not effective in terms of students’ achievement but is effektif in terms of students’ learning motivation, and (3) the STAD type cooperative learning model is more effective than the conventional teaching in terms of improved students’ learning and achievement but it is not more effective in terms of increasing the motivation.Keywords: STAD, achievement, learning motivation.